2022
DOI: 10.21203/rs.3.rs-2034404/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Earliest evidence for hunter-gatherer impacts on raven diet and ecology in the Gravettian of Southern Moravia

Abstract: The Early Gravettian of Southern Moravia – the Pavlovian – is notable for its corvid-rich faunal assemblages dominated by common ravens (Corvus corax). Based on the available zooarchaeological and settlement data from the Pavlovian, it has been hypothesized that ravens were attracted by human domestic activities and subsequently captured by Pavlovian people for food and feathers. Here, we report independent δ15N, δ13C and δ34S isotope data obtained from twelve adult common ravens from the Pavlovian key sites o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…The listed cases are all linked to forager societies of the Late Pleistocene and early/middle Holocene; 'state of knowledge' refers to the quality and reliability of palaeosynanthropic archaeological evidence, from low (+) to reasonable (+++).candidate animal speciesarchaeological contexthypothesized/expected human–environmental feedback systemstate of knowledgeliteraturecommon raven ( Corvus corax ), Arctic fox ( Vulpes lagopus )Pavlovian (earlier Gravettian/mid–Upper Palaeolithic of Moravia); ca 31 to 27 kyaUnusual site fidelity and recurrent mammoth hunting attract opportunistic scavengers that are in part deterred and in part promoted, in turn shaping human cultural behaviour and so creating complex, spatially heterogeneous ecologies with patches of biodiversity hotspots (integrated mammoth-based foraging). Foxes and ravens feature in human cultural practices.+++[54,187–192]red fox ( Vulpes vulpes ), Arctic foxAurignacian and Gravettian (pre-LGM Upper Palaeolithic of southwestern Germany (Swabian Jura)); ca 42 to 30 kyaIntensive human settlement and large herbivore hunting (esp. reindeer, Rangifer tarandus ) and selective body-part transport provide scavenging opportunities for small scavengers such as foxes, which are apparently tolerated by hunter–gatherers.…”
Section: The Palaeo-synanthropic Niche As Human Ecosystem Servicementioning
confidence: 99%
See 4 more Smart Citations
“…The listed cases are all linked to forager societies of the Late Pleistocene and early/middle Holocene; 'state of knowledge' refers to the quality and reliability of palaeosynanthropic archaeological evidence, from low (+) to reasonable (+++).candidate animal speciesarchaeological contexthypothesized/expected human–environmental feedback systemstate of knowledgeliteraturecommon raven ( Corvus corax ), Arctic fox ( Vulpes lagopus )Pavlovian (earlier Gravettian/mid–Upper Palaeolithic of Moravia); ca 31 to 27 kyaUnusual site fidelity and recurrent mammoth hunting attract opportunistic scavengers that are in part deterred and in part promoted, in turn shaping human cultural behaviour and so creating complex, spatially heterogeneous ecologies with patches of biodiversity hotspots (integrated mammoth-based foraging). Foxes and ravens feature in human cultural practices.+++[54,187–192]red fox ( Vulpes vulpes ), Arctic foxAurignacian and Gravettian (pre-LGM Upper Palaeolithic of southwestern Germany (Swabian Jura)); ca 42 to 30 kyaIntensive human settlement and large herbivore hunting (esp. reindeer, Rangifer tarandus ) and selective body-part transport provide scavenging opportunities for small scavengers such as foxes, which are apparently tolerated by hunter–gatherers.…”
Section: The Palaeo-synanthropic Niche As Human Ecosystem Servicementioning
confidence: 99%
“…Recent work on the Moravian Pavlovian in the Czech Republic ( ca 31–27 kya) has revealed that common ravens ( Corvus corax ), unusually abundant in zooarchaeological assemblages of the region, developed dietary preferences closely aligned with those of contemporary human foragers, consuming primarily large herbivores such as bison and horse (but not reindeer) and especially mammoth, animals also preferentially targeted by their human neighbours [54]. This evidence coincides with a number of substantial changes in human behaviour when compared to the earlier Upper Palaeolithic settlement in the region.…”
Section: The Palaeo-synanthropic Niche As Human Ecosystem Servicementioning
confidence: 99%
See 3 more Smart Citations